Impact of indium substitution on dielectric and magnetic properties of Cu0.5Ni0.5Fe2-xO4 ferrite materials. Issue 10 (July 2019) - Junaid, Muhammad; Khan, Muhammad Azhar; Akhtar, Majid Niaz; Hussain, Altaf; Warsi, Muhammad Farooq
Abstract: Indium substituted CuNi nanoferrites with nominal compositions Cu0.5 Ni0.5 Inx Fe2-x O4 (x = 0.00–0.32) were successfully synthesized by sol-gel auto ignition method. X-ray diffraction patterns illustrated the single phase spinel structure for x ≤ 0.24. The lattice parameter 'a' increased from 8.3349 to 8.3723 Å and then it decreased for x = 0.32. X-ray density increased from 5.43 to 5.79 g/cm 3 . The average crystallite sizes lie in the range 33.21–17.78 nm. The cell volume was increased from 579.03 to 586.86 Å 3 with the substitution of indium ions into the spinel lattice of copper nickel ferrites. The compositional dependence of tetrahedral and octahedral radii was explained on the basis of lattice parameter. The incorporation of In 3+ ions in copper nickel ferrites exhibited the decreased in bulk density. The dielectric parameters were explained over entire range of frequency (1M-3 GHz). The dielectric parameters i.e dielectric constant, dielectric loss and tan loss were found to decrease with the increase of indium concentration. The saturation magnetization (Ms ) and Bohr magneton (nB ) first increased and then decreased. The remanence (MR ) was increased with the substitution of indium ions. The coercivity and anisotropy constant were decreased which might be due to weak A-B super exchange interaction. The results of magnetic and dielectric properties suggested that In 3+ substituted copper nickel ferries are suitable for high frequency applications.